Corrosion and Protection of Silicon Nitride Insulators in Microelectrode Array Applications - Karttu, Antti; Lahtonen, Kimmo; Heikkila, Juha; Valiaho, Jari; Narkilahti, Susanna; Lekkala, Jukka; Kallio, Pasi (IEEE sensors journal, 2022)
In the study of the electrophysiological activity of cultured cells, the integrity of the electrical insulation layer is crucial in ensuring the reliability of microelectrode array (MEA) sensor measurements. The materials used are required to withstand the challenging culture conditions for up to several months. The commonly used silicon nitride (SiN) has been reported to corrode in cell cultures with very little attention in the scientific community. Herein, we show that plasma-enhanced chemical vapor deposited (PECVD) SiN is subject to substantial wear when in contact with different culture media, with the corrosion rate depending on the deposition temperature and media type. A chemically stable insulator is proposed and demonstrated as an alternative for SiN using thermally annealed atomic layer deposited (ALD) titanium dioxide (TiO 2 ) as a transparent protective layer for SiN. Electrochemical impedance spectroscopy (EIS) was successfully applied to periodically assess the integrity and thickness of the insulation layers in two different media, with profilometer measurements performed as an endpoint analysis to confirm the actual change in thickness in four solutions. ALD TiO 2 not only prevented insulator corrosion but also showed excellent cytocompatibility during a four-week culture with human embryonic stem cell (hESC)-derived neurons. The results here underline the need for addressing the corrosion of SiN insulation in MEA sensors. We believe that the integrity and results of cellular measurements can be compromised, especially when reusing MEAs. We propose the ALD TiO 2 protected insulator as a viable solution for this problem, as it increases reliability, particularly during extended cell cultures.